SUSTAINABLE DEVELOPMENT OF RENEWABLE ENERGY IN SHIPPING: TECHNOLOGICAL AND ENVIRONMENTAL PROSPECTS - Oleksiy MELNYK; Mykola BULGAKOV; Oleksij FOMIN; Svitlana ONYSHCHENKO; Oleg ONISHCHENKO; Igor PULYAEV (Scientific Journal of Silesian University of Technology. Series Transport, 2025)
Shipping is one of the major sources of greenhouse gas emissions; therefore, immediate actions must be taken in the field of sustainable development. This study focuses on exploring the use of renewable energy to mitigate emissions and enhance energy efficiency on board ships. Hence, technologies for capturing, utilizing, and storing solar, wind, and carbon energy are investigated. Further, the study weighs these approaches in terms of benefits, drawbacks, and potential application in sustainable maritime operations. To quantify the practicability of the solutions analyzed, an interdisciplinary approach intertwining feasibility analysis, simulation modeling, and policy evaluation is used. Topics discussed include technological barriers, economic barriers, and regulatory frameworks. It also highlights recent advances with great environmental potential in shipping, such as hybrid propulsion systems and fuel cell technologies. The results showed that the hybrid systems with renewable energy combined with CCUS can reduce CO₂ emissions from ships up to 90%, which, in the best case, simultaneously imparts an increased operational efficiency and environmental sustainability. The study therefore examined regulatory and policy options that could facilitate the transition to renewable energy in this sector, and the industrial application of these technologies is thus presented as a key stage in environmentally sustainable development.